Factors influencing women’s choice of health care provider during childbirth in Port Harcourt, Southern Nigeria - Kasso, Terhemen; Asuquo, Gregory W. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Maternal mortality is high in sub-Saharan African countries. Maternal deaths are preventable if births are attended by skilled health care providers who can manage complications promptly when they arise. Some women however patronise traditional birth attendants who contribute to maternal mortality in Nigeria due to their inability to manage complications during and after delivery. The aim of this study was to ascertain the factors influencing women’s choice of healthcare provider during childbirth and their effect on maternal mortality in Port Harcourt, Rivers State, Nigeria. Methods: A descriptive cross-sectional design was used to elicit information from mothers attending postnatal and immunization clinics at University of Port Harcourt Teaching Hospital. An interviewer-administered questionnaire was used to obtain information and the data collected was analysed using statistical package for social sciences (SPSS) version 22 and presented as frequencies and percentages in tables and charts. Results: The study revealed that 90.5% of the respondent’s identified obstetricians as the most skilled for delivery and most (91.5%) had utilized their services. Majority (93.5%) had good perception about obstetricians, 54.5% were not satisfied with the cost of their services stating that it was expensive. Some factors identified to influence delivery with TBAs were cheap services, ignorance, belief system, easy accessibility, availability and lesser time consumption. Conclusions: Cheap TBA services attracted women to their utilisation. Reduction in the cost of modern obstetric services will enhance their utilization, improve obstetric outcome and reduce maternal deaths.